2017
DOI: 10.11648/j.ijsd.20170303.12
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies of Statistical Analysis in Engineering

Abstract: Statistical analysis finds a wide range of applications in scientific research, management, finance, and engineering. In this article, we aim at shedding some light on the significance of two tools of statistical analysis, namely ANOVA and regression, in civil (including environmental), mechanical, and architectural engineering disciplines through a short survey of recent research studies that utilized these tools to reach important engineering models or rules of interest to engineers for design or development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…According to the data obtained in the table above, the mean delays in the completion of activities differed. It can therefore be concluded that there were statistically significant differences between the projects with respect to the delay variable, since F(4.5140) = 274.3 (not equal to 1), with p < 0.05 (2 × 10 −16 ) [54,61]. This was the expected result, given the non-uniform nature of the projects and their source data.…”
Section: One-way Analysis Of Variance (Anova)mentioning
confidence: 63%
See 2 more Smart Citations
“…According to the data obtained in the table above, the mean delays in the completion of activities differed. It can therefore be concluded that there were statistically significant differences between the projects with respect to the delay variable, since F(4.5140) = 274.3 (not equal to 1), with p < 0.05 (2 × 10 −16 ) [54,61]. This was the expected result, given the non-uniform nature of the projects and their source data.…”
Section: One-way Analysis Of Variance (Anova)mentioning
confidence: 63%
“…The following results were obtained with weighted variables as shown in Table 7. In this model, the p-values that help to resolve these contrasts were in both cases, 2 × 10 −16 , a value less than 0.05 [54,55]. Thus, considering a significance level of 5%, the null hypothesis would be rejected in both cases, concluding that there was a linear relationship between the variables.…”
Section: Delay Finishmentioning
confidence: 87%
See 1 more Smart Citation